La rebelión de los tibios. Dos reacciones anti-progresistas en la Francia de inicios del siglo XXI - José Antonio Rubio Caballero (Amnis)
Ideological apathy has aroused little interest among historians and sociologists. Faced with the active vanguards, the abstentionist or passive masses tend to escape the radars of the academy. However, these crowds have also had their moments of influence, causing doubts among scholars, who, accustomed to handling clear schemes, hesitate when interpreting phenomena that are difficult to catalog, carried out by these "neutral masses”. Due to its unusual nature, it is convenient to observe two French actual phenomena carried out by actors normally installed in civil discretion: the Manif pour Tous and the Gilets Jaunes.